TINJAUAN YURIDIS KESINAMBUNGAN PEMBANGUNAN IBU KOTA NEGARA NUSANTARA BERDASARKAN SISTEM PERENCANAAN PEMBANGUNAN NASIONAL - Fadriyatun, (2023)
The Government of the Republic of Indonesia has stipulated the transfer of the National Capital in North Paser Regency, East Kalimantan. The transfer process officially began when Law Number 3 of 2022 concerning the National Capital was passed. The enactment of Law Number 3 of 2022 concerning the National Capital has reaped Pros and Cons in the community and even repeatedly submitted to the Constitutional Court. Meanwhile, the government is trying to respond by revising Law Number 3 of 2022 concerning the National Capital. This shows its unpreparedness as a legal instrument that can provide legal certainty for the continuity and continuity of the development of the National Capital of the Archipelago. The problems raised in this study are how to guarantee legal certainty of the continuity of development of the National Capital of the Archipelago and how to strengthen the continuity of development of the National Capital of the Archipelago. This research uses normative juridical research methods using a conceptual approach. From the research that has been carried out, it can be concluded that the Capital City of the Archipelago has the potential to have no continuity in its implementation so that the development of the National Capital City must be in accordance with the National Development Planning System (SPPN) Law and accommodated in the National Long-Term Development Plan (RPJPN) Law 2025-2045 so that the development of the National Capital of the Archipelago can be carried out thoroughly, integratedly, directed, and sustainable in realizing the vision and mission of the Republic of Indonesia.